2008
DOI: 10.1371/journal.pgen.1000110
|View full text |Cite
|
Sign up to set email alerts
|

Alternative-NHEJ Is a Mechanistically Distinct Pathway of Mammalian Chromosome Break Repair

Abstract: Characterizing the functional overlap and mutagenic potential of different pathways of chromosomal double-strand break (DSB) repair is important to understand how mutations arise during cancer development and treatment. To this end, we have compared the role of individual factors in three different pathways of mammalian DSB repair: alternative-nonhomologous end joining (alt-NHEJ), single-strand annealing (SSA), and homology directed repair (HDR/GC). Considering early steps of repair, we found that the DSB end-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

46
999
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 754 publications
(1,051 citation statements)
references
References 49 publications
46
999
6
Order By: Relevance
“…NHEJ protein KU80. 22 This was also observed under our experimental settings (Fig. S1D), thus validating the sensitivity of our method.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…NHEJ protein KU80. 22 This was also observed under our experimental settings (Fig. S1D), thus validating the sensitivity of our method.…”
Section: Introductionsupporting
confidence: 86%
“…To this end, we initially exploited a system enabling us to assess the efficiency of homology directed repair by single-strand annealing (SSA). 22 In a similar fashion to the DR-GFP system, this assay relies on the restoration of a GFP gene that also presents an I-SceI cutting site, which is truncated by the insertion of 2.7 Kb DNA fragment. When the DSB is induced by I-SceI transfection, the 2.7 kb fragment is removed Herein, using specific DNA repair assays and exploring the recruitment of key repair proteins to sites of DNA damage in mammalian cells, we show that HP1 paralogs impact differentially on the DDR, leading both to inhibition and stimulation of the repair of double-stand breaks (DSBs) by homologous recombination.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies suggest that in yeast, Srs2 helicase, Sae2 nuclease [CtBP-interacting protein (CtIP) homologue], Tel1 [ataxia telangiectasia mutated (ATM) homologue], and DNA polymerases (Pol4, Rev3, and Pol32) are important for MMEJ (11). In mammalian cells, Mre11, CtIP, and DNA ligase III have critical roles in MMEJ (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…SSA efficiency is known to be elevated in situations where RAD51 function has been generally disrupted. 27,28 Similarly, we previously demonstrated that both RI-1 and RI-2 induce elevated levels of SSA activity. 19 By contrast, we found that 9h does not stimulate SSA, using a relevant concentration range that inhibits HR (Figure 5b).…”
Section: Optimization Of Ring Amentioning
confidence: 64%
“…27 Briefly, cells containing the chromosomal DR-GFP reporter were transfected with a plasmid that expresses I-SceI, a rare-cutting endonuclease that makes a DSB within the DR-GFP cassette. Compounds were added at the time of transfection, and the cells were outgrown for 24 h. We noted that for longer outgrowth periods such as 48 h, cells regained some HR activity (data not shown).…”
Section: Optimization Of Ring Amentioning
confidence: 99%